Contemporary Role of Topical Calcineurin Inhibitors: A Pediatric Dermatology Perspective. Issue 4 (September 2019) - Fiorillo, Loretta; Marcoux, Danielle; Ramien, Michele
Atopic dermatitis (AD) is the most common pediatric chronic inflammatory skin disease in North America, often involving complex treatment regimens and impairing the quality of life of affected children and their families. Two topical calcineurin inhibitors (TCIs) have been available for the treatment of AD in pediatric patients for more than 15 years, and they continue to represent an important steroid-sparing option for the management of AD. Despite the large body of evidence and extensive clinical experience with these agents, there remain concerns among parents and clinicians regarding the long-term safety of this class of therapy, particularly with respect to the boxed warning about the potential risk of lymphoma and malignancy associated with TCIs. Concerns about burning or stinging with initial applications are also common. This review examines the literature on the clinical effectiveness of TCIs, with a focus on the pivotal research that supports the efficacy of these agents, and the reassuring body of evidence supporting their long-term safety in pediatric patients. Practical recommendations for maximizing the utility of TCIs in pediatric patients, including discussion points to address with parents, are offered.